PERSEPSI ORANG TUA TENTANG BOARDING SCHOOL - Afni Dwi Ulfa; Muchammad Eka Mahmud; Mohammad Salehuddin (Management of Education: Jurnal Manajemen Pendidikan Islam, 2023)
This article aims to observe perceptual information from parents about boarding schools. This study uses a quantitative approach to the survey method. The subjects of this study were parents whose children lived in the boarding school environment as a data source. The results of this study indicate that parents have a positive perception of boarding school. Parents understand the function, purpose and benefits of boarding school.